Legal Protection of Banks as Creditors in Credit Agreements with Overlapping Land Guarantees - Tirsa Amadea Azarin; Jamal Wiwoho; Arief Suryono (Siber International Journal of Advanced Law (SIJAL), 2025)
A credit agreement is an agreement between the debtor and the creditor. The creditor has the right to seize the collateral if the debtor defaults or does not fulfill his obligation to repay the debt. If it is found that the condition of the collateral object is a plot of land with multiple or overlapping certificates, the creditor needs protection to overcome this. Likewise, the debtor is responsible for replacing the lost collateral object because the collateral object is a plot of land with multiple certificates. This research is prescriptive normative research, conducted with a statutory approach and tracing legal materials using literature studies or library research. The data used is secondary data in the form of primary legal materials, secondary legal materials, and non-legal materials. The results of this study found a solution that in Article 1131 of the Civil Code states that the credit agreement binds all of the debtor's assets. Thus, if the debtor defaults and the collateral object cannot be executed, the creditor can file a lawsuit for the replacement of the collateral object followed by a collateral seizure. The debtor is also responsible for replacing the collateral, to fulfill the creditor's rights.